Selective human Estrogen Receptor Partial Agonists (ShERPAs) for Tamoxifen-Resistant Breast Cancer - Xiong, Rui (J Med Chem, 2015)
Almost 70% of breast cancers are estrogen receptor α (ERα) positive. Tamoxifen, a selective estrogen receptor modulator (SERM), represents the standard of care for many patients; however, 30-50% develop resistance, underlining the need for alternative therapeutics. Paradoxically, agonists at ERα such as estradiol (E(2)), have demonstrated clinical efficacy in patients with heavily-treated breast cancer, although side effects in gynecological tissues are unacceptable. A drug that selectively mimics the actions of E(2) in breast cancer therapy, but minimizes estrogenic effects in other tissues is a novel, therapeutic alternative. We hypothesized that a selective human estrogen receptor partial agonist (ShERPA) at ERα would provide such an agent. Novel benzothiophene derivatives with nanomolar potency in breast cancer cell cultures were designed. Several showed partial agonist activity, with potency of 0.8-76 nM, mimicking E(2) in inhibiting growth of tamoxifen-resistant breast cancer cell lines. Three ShERPAs were tested and validated in xenograft models of endocrine-independent and tamoxifen-resistant breast cancer, and, in contrast to E(2), ShERPAs did not cause significant uterine growth.